Pengaruh Kreativitas Verbal terhadap Keterampilan Berbicara pada Mahasiswa Program Studi Psikologi Universitas Negeri Manado - Tellma M. Tiwa (Jurnal Ilmiah Wahana Pendidikan, 2023)
Verbal creativity is one of the factors that can support a person's speaking skills apart from other factors. Speaking skills are the ability to express thoughts and ideas in the mind accompanied by good speaking expression and conveying ideas. The aim of this research is to find out whether there is an influence of verbal creativity on speaking skills in psychology students at Manado State University. In this research, quantitative correlational research was used. The subjects in this research were psychology study program students in semesters III and V, class of 2015 and 2016. The sampling technique used was cluster random sampling of 10%. And the total sample size was 38 psychology students. The instruments used were verbal creativity tests and speaking skills scales. And in this research, the data analysis technique used in hypothesis testing is a simple regression analysis technique by testing the data using the SPSS 24.0 for Windows tool. The results of this research showed that "There is an influence of verbal creativity on students' speaking skills." After testing using simple regression analysis, the Regression equation Ŷ = 30,149 +.461 This comparison shows that if there is an increase of one time/unit or 100 times/unit in the verbal creativity variable, there will be an increase of 0.46 or 46/unit in the speaking skill variable. Judging from the Fcount value obtained, it is 18.755, which is greater than the p value (probability of error) of 0.000, which means it is smaller than 0.05. This means that the higher the verbal creativity, the more positive and significant it will have on improving the speaking skills of FIP Unima psychology students